2016
DOI: 10.14710/jkli.14.2.45-50
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Perilaku Ibu dan Lingkungan Fisik Rumah dengan Kejadian Tuberkulosis Paru Anak di Kota Pekalongan

Abstract: Background: Children's Tuberculosis (TB) (p = 0.049; OR = 2.918; 95% CI = 1.005 to 8.472), density occupancy (p = 0.020; OR = 3.379; 95% CI = 1.212 to 9.417), humidity (p = 0.025; OR = 3.236; 95% CI = 1.156 to 9.058) and ventilation (p = 0.022; OR = 3.224; 95% CI = 1.182 to 8.797). Conclusion:The density occupancy, humidity, ventilation, mother's knowledge are a risk factor pulmonary TB incidence of children in Pekalongan City.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 3 publications
1
6
0
8
Order By: Relevance
“…The results of this study are in line with the results of research by Mudiyono (2015) which states that the type of floor is not related to the incidence of Tuberculosis in children with p value = 0.552. 11 The results of this research in line with the research result of Zia Faizaty (2018) which mentions the floor type is not related to the incidence of TB children with p value = 1.000. 7 Than cooking fuel is categorized as a proper cooking fuel if it is from electricity and LPG.…”
Section: Discussion:-supporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study are in line with the results of research by Mudiyono (2015) which states that the type of floor is not related to the incidence of Tuberculosis in children with p value = 0.552. 11 The results of this research in line with the research result of Zia Faizaty (2018) which mentions the floor type is not related to the incidence of TB children with p value = 1.000. 7 Than cooking fuel is categorized as a proper cooking fuel if it is from electricity and LPG.…”
Section: Discussion:-supporting
confidence: 90%
“…The risk for the occurrence of Tuberculosis in children in respondents with ventilation that does not meet the requirements 3.4 times greater than the respondents who have ventilation that meets the requirements. 11 Adverse children life environmental conditions, as high humidity and poor ventilation can increase the risk of TB. 12 Based on this study there is a significant correlation between lighting and the incidence of Tuberculosis in children in Sumedang Regency.…”
Section: Discussion:-mentioning
confidence: 99%
“…The results of 7 journals show that statistically the research results are as follows (p-value=0.001;95%CI) [11]; (p-value = 0.000; OR = 0.113; CI 0.001-1.301) [9]; (p-value=0.000; OR=6.67; 95%CI=2.44-18.21) [12]; (p-value=0.001; OR:6,641, 95% CI: 2,769-15,927) [13]; (OR=2.455> 1) [14]; (p-value= 0.02; OR=4.3; 95% CI 1.39-12.95); [15] and one journal discussing univariately showed that 5 respondents with pulmonary TB (100%) had a residential density that did not meet the requirements, 5 respondents who did not have TB (50%) had a residential density that did not meet the requirements [3].…”
Section: Occupancy Densitymentioning
confidence: 99%
“…The results of the study were successively with a degree of significance (p-value) < 0.05. Statistical results of room humidity value (p-value = 0.012) [11]; (p-value=0.001; OR=5.17; 95% CI=1.95-13.70) [12]; Humidity (p-value=0.001; OR=6,000; 95% CI=2.528-14.240) [13]; (p-value = 0.015; OR = 4.25; 95% CI = 1.33-13.56) [17] and one journal with univariate analysis showed that 4 respondents with pulmonary TB (80%) had humidity that did not meet the requirements and 4 control respondents (40%) do not have the humidity that meets the requirements. The results of these studies show that someone who lives in humidity that does not meet the requirements can have a risk of developing pulmonary TB by 4.25 -6 times more risk than someone who lives in humidity that meets the requirements.…”
Section: Humiditymentioning
confidence: 99%
“…Tingkat pengetahuan ibu tentang tuberkulosis paru pada anak akan mempengaruhi pula perilaku pencegahan terhadap TBC paru pada anak (Ernawati, 2016). Penelitian lain yang dilakukan di Kota Pekalongan menyebutkan bahwa terdapat hubungan antara pengetahuan, sikap serta perilaku ibu terhadap pencegahan TBC paru dengan kejadian kasus TBC paru pada anak (Mudiyono, 2015).…”
unclassified